PENINGKATAN KETERAMPILAN BERPIDATO PERSUASIF DENGAN METODE SPEAKING TEAM PADA SISWA KELAS IX B MTS NEGERI 2 LAMONGAN TAHUN PELAJARAN 2023/2024 - Zumrotul Ilmiyah (Pendidikan Bahasa dan Sastra Indonesia, 2023)
This research aims to improve persuasive speech skills using the speaking team method in class IX B students at MTs Negeri 2 Lamongan. The method used in this research is a qualitative method with the type of classroom action research. This research was carried out in two cycles. Each cycle is designed and implemented with the steps 1) planning, 2) action, 3) observation, and 4) reflection. The data source in the research is the implementation of the persuasive speech learning process which took place in class IX B MTs Negeri 2 Lamongan, while the data in the research is in the form of scores obtained by students during the persuasion speech learning implementation. Data is analyzed by calculating certain statistics such as averages which are explained using tables. The results of the research showed that students' persuasive speech abilities increased on average in cycle 1 by 74%, including in the fair category, increasing to 91% in cycle 2, including in the good category.